The p.P479L variant in CPT1A is associated with infectious disease in a BC First Nation. Issue 2 (6th August 2018) - Sinclair, Graham; Collins, Sorcha; Arbour, Laura; Vallance, Hilary
Abstract: Background: The hepatic carnitine palmitoyltransferase I ( CPT1A ) p.P479L variant is common in Aboriginal populations across coastal British Columbia, Alaska, the Canadian North, and Greenland. While the high frequency of this variant suggests positive selection, other studies have shown an association with sudden unexpected death in infancy and infection. We utilized administrative health data to evaluate hospitalizations for a single year cohort of children of First Nations descent genotyped for the variant and, matched for location of birth. Seven years of data were reviewed for 150 children split evenly between CPT1A genotypes (homozyous, heterozygous, and noncarrier of the p.P479L variant). Results: Children homozygous for the p.P479L allele had a higher rate of hospital admissions at 2.6 per individual as compared to noncarriers at 0.86. Heterozygous children also showed a significant increase at 1.9 per person. Length of stay per admission was increased for both p.P479L homozygotes and heterozygotes. The odds ratio (OR) for at least one hospitalization for any reason was increased for p.P479L homozygotes relative to noncarriers (OR=10.2, confidence interval [CI] 3.5 to 30.0) as were admissions for dental caries (OR=3.4, CI 1.5 to 7.8), acute lower respiratory tract infections (OR=6.0, CI 1.6 to 22.4), and otitis media (OR=13.5, CI 1.7 to 109.4). Conclusions: The CPT1A p.P479L variant is associated with an increased rate of hospitalization for those homozygous, primarily for infectious disease causes. Heterozygotes also showed a small but significant increase in hospitalization rates suggesting some dosage effect. Functional studies will be required to identify the underlying pathological mechanism.